Investigation of pain and analgesic strategies in food animals - Martin, Miriam Sharon (Kansas State University, 2021)
Food animals are stoic by nature and have long been subject to evolutionary pressure to mask pain to avoid becoming prey. Quantifying pain via biomarkers allows researchers to capture changes that are not easily detected by the human eye. Negative public perception of pain associated with routine husbandry practices such as dehorning and castration is growing, increasing the need for the development of practices to relieve pain and suffering in livestock. Pre-emptive analgesia can be applied in advance of the painful stimulus, which reduces sensitization of the nervous system to stimuli that could amplify pain. Further research into the development of appropriate behavioral and physiological pain assessment tools is needed to objectively quantify pain and search for the most effective analgesic strategies. In this dissertation, the diagnostic sensitivity and specificity of pain biomarkers is investigated across different collection time points and varying painful procedures and conditions including surgical castration, dehorning, lameness, abdominal surgery, and bovine respiratory disease using receiver operating characteristic (ROC) curves. The analgesic effects of flunixin transdermal on pain biomarkers, performance and health indicators are evaluated in feeder calves. Pain associated with induced bacterial pneumonia, scoop and hot-iron dehorning, surgical castration, and hot-iron branding is characterized. The effectiveness of bupivacaine liposome suspension, administered prior to dehorning and castration, to alleviate pain is compared to a multi-modal approach of lidocaine and meloxicam. The effect of meloxicam on pain biomarkers following hot-iron branding is explored. The pharmacokinetics of flunixin meglumine administered intramuscularly and meloxicam administered orally or intramuscularly in juvenile tilapia is described. Results comparing nonsteroidal anti-inflammatory drug (NSAID) analgesic effects to uncontrolled pain consistently yielded good diagnostic accuracy for plasma cortisol, hair cortisol and infrared thermography. Biomarkers that yielded good diagnostic accuracy for predicting calves with significant lung lesions in the first 72 h after bovine respiratory disease (BRD) onset include, right front stride length, gait velocity, visual analog scale score, clinical illness score, average activity level, step count and rectal temperature. After 72 post-induction, prostaglandin E₂ metabolite, gait distance, cortisol, infrared thermography, right front force, average activity level, step count and serum amyloid A yielded the best diagnostic accuracy for predicting the severity of lung lesions. Results suggest there were no significant advantages in performance, health, or activity measured by accelerometers from the co-administration of flunixin meglumine transdermal and tildipirosin. However, calves co-administered flunixin meglumine transdermal and tildipirosin did have lower visual analog scale scores indicating that less pain was apparent the first 36 hours post-drug application relative to calves only administered tildipirosin. A combination of reduced activity levels, decreased force on calves’ right front limb, and increased visual analog scale pain scores all support that bacterial pneumonia in cattle is painful. Differences in right front force were observed in calves challenged with M. haemolytica and treated with flunixin transdermal and those given a placebo, indicating that flunixin transdermal may attenuate specific pain biomarkers in cattle with BRD. Our results indicate that pain from cautery dehorning can last up to 120 h post-dehorning indicated by changes in nociception and gait analysis. Evidence provided in the current study demonstrates that pain from surgical castration can last up to 120 h post-castration, indicated by changes in ocular temperature, gait analysis, and prostaglandin E₂ metabolite concentrations. These data show that administration of bupivacaine liposome suspension as a local anesthetic block at the time of dehorning and castration was as effective at controlling pain as a multi-modal approach of lidocaine and meloxicam. Results suggest that lidocaine + meloxicam reduces cortisol and prostaglandin metabolite concentrations at certain timepoints more than ethanol + lidocaine or bupivacaine liposome suspension + lidocaine administered as a local infiltration and cornual block prior to scoop dehorning followed by cauterization. The treatments administered in the present study did not significantly extend the duration of analgesia beyond the currently recommended multi-modal approach, including local anesthesia and systemic analgesia such as lidocaine and meloxicam. Results suggest that sex influences certain pain biomarkers specifically nociceptive threshold and cortisol concentration, with males having a higher nociceptive threshold and lower cortisol responses. These results show that infrared thermography, mechanical nociceptive threshold, lying time, step count, visual analog scale score and wound scoring all support that hot-iron branding cattle is painful and investigation into analgesic strategies is needed. Oral meloxicam administration reduced infrared thermography differences from the branding and control site and reduced lying bouts. Breed and sex effects were observed across a wide range of biomarkers. In juvenile Nile tilapia, flunixin administered intramuscularly reached sufficient plasma concentrations to potentially have an analgesic effect, while meloxicam administered either intramuscularly or orally at the given dosage likely did not have an effect due to the relatively low plasma concentration. The feasibility of dosing individual fish is limited in commercial operations but may be relevant to settings where individual fish are more valuable and are handled on occasion. Development of an effective granular formulation of an NSAID would be more likely to be integrated into commercial operations. In conclusion, these results indicate that ROC analysis can be an indicator of the predictive value of biomarkers associated with pain and inflammation. The need for long-acting analgesic options for cattle that demonstrate pain alleviation across multiple biomarkers is apparent and would be beneficial to alleviating pain from routine husbandry procedures like dehorning, castration, and branding, as well as painful disease conditions such as bovine respiratory disease. Breed and sex effects were observed across a wide range of biomarkers and should be investigated in future pain studies. Further studies investigating different drug concentrations and dosage regimens of meloxicam, as well as clinical efficacy of flunixin and meloxicam in Nile tilapia are warranted to provide effective options for pain control in fish.
Keywords: Cattle; Pain; Analgesia; Nonsteroidal anti-inflammatory drug; Local anesthetic; Welfare